1990
DOI: 10.1021/jf00102a012
|View full text |Cite
|
Sign up to set email alerts
|

Application of thermoluminescence measurements to detect irradiated strawberries

Abstract: The thermoluminescence intensity of unirradiated and irradiated strawberries was studied with regard to dose response, storage time, and different varieties. An identification method could finally be developed. Further investigations were carried out to determine the origin of the thermoluminescence effect, which was found to be attributable to mineral grains adhering to the sample surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1993
1993
2004
2004

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…It may be useful to combine TL measurements with some other methods like viscosity determination etc. as suggested by Heide et al [16]. The combination of results from two or more experimental techniques would then be more reliable conclusive and particularly important in view of wide variations in the TL response.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…It may be useful to combine TL measurements with some other methods like viscosity determination etc. as suggested by Heide et al [16]. The combination of results from two or more experimental techniques would then be more reliable conclusive and particularly important in view of wide variations in the TL response.…”
Section: Resultsmentioning
confidence: 85%
“…Earlier reports claimed that TL is one of the several techniques recommended for adaptation as reliable and simple identification method for herbs, spices and fruits [9,11,12]. Some other workers [13] Experiments were conducted to see the effect of irradiation on the thermoluminescence emission from dust of plant nuts such as almond, peanut, pinenut and walnut.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be useful to combine TL measurements with some other methods like viscosity etc. as suggested by HEIDE et al 13 The combination of results from two or more experimental techniques would then be more reliable, conclusive and particularly important in view of wide variations in the TL response. The data in our studies were obtained after 15 days of irradiation treatment and it was concluded that irradiation treatment profoundly increased the TL intensities in dried apricots dates and raisins and the results were significantly dose dependent and that TL measurements with properly separated minerals can possibly be employed for identification as well as measurement of absorbed dose in irradiated dried fruits.…”
Section: Resultsmentioning
confidence: 93%